2021
DOI: 10.31234/osf.io/rh9jy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suicidality and Mood: The Impact of Trends, Seasons, Day of the Week, and Time of Day on Implicit and Explicit Cognitions

Abstract: Decades of research have established seasonality effects on completed and attempted suicides, with an increase in rates during spring and early summer. Using more than six years of data (April 2012 – November 2018), we used new Prophet models to forecast mood and explicit and implicit measures of self-harm among an online community sample residing in the US and UK (N > 7,975). We decomposed the time series into trends across the years, within years (seasons), weekly, and daily seasonal patterns. Across … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Decades of research have identified several key risk factors for suicide, including past psychiatric disorders, such as depression (Chesney et al., 2014), past self‐harm behavior, suicide cognitions (Chan et al., 2016), and different sociodemographic factors, such as being middle‐aged (Berkelmans et al., 2021). Research has also identified more distal population‐wide risk factors associated with increased risk for suicidal behavior, including economic turmoil (Turecki & Brent, 2016), and seasonality (Freichel & O’Shea, 2023), with increases in deaths by suicide in spring (Christodoulou et al., 2012). In particular, the field has gained a better understanding of explicit cognitions (e.g., negative affect, Gee et al., 2020) and psychophysiological processes (e.g., sleep, Brüdern et al., 2022) in their prediction of daily self‐harm behavior and suicide cognitions, thanks to the modern‐day abundance of smartphones and the associated popularity of ecological momentary assessment in suicide research (Kleiman et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Decades of research have identified several key risk factors for suicide, including past psychiatric disorders, such as depression (Chesney et al., 2014), past self‐harm behavior, suicide cognitions (Chan et al., 2016), and different sociodemographic factors, such as being middle‐aged (Berkelmans et al., 2021). Research has also identified more distal population‐wide risk factors associated with increased risk for suicidal behavior, including economic turmoil (Turecki & Brent, 2016), and seasonality (Freichel & O’Shea, 2023), with increases in deaths by suicide in spring (Christodoulou et al., 2012). In particular, the field has gained a better understanding of explicit cognitions (e.g., negative affect, Gee et al., 2020) and psychophysiological processes (e.g., sleep, Brüdern et al., 2022) in their prediction of daily self‐harm behavior and suicide cognitions, thanks to the modern‐day abundance of smartphones and the associated popularity of ecological momentary assessment in suicide research (Kleiman et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…display how information about situations can be leveraged for individual prediction of behaviors and experiences and discuss the relevance of situation information for personality research, whileCloos et al (2022) use the sensitivity to emotionally relevant events as a quality criterion for EMA items. Both weekend effects and time-of-day effects have been studied across a range of constructs (see, e.g.,Freichel and O'Shea (2021) for suicide and mood orEgloff et al (1995) for positive affect) Gabriel et al (2019). offer a discussion on time trends and how to model them, whileZhang and Volkow (2023) discuss the role of seasonality and circadian rhythms in psychiatric disorders.…”
mentioning
confidence: 99%